ТЕХНІКО-ЕКОНОМІЧНІ ОЦІНКИ ВИРОБНИЦТВА ЕЛЕКТРОЕНЕРГІЇ ФОТОЕЛЕКТРИЧНИМИ СТАНЦІЯМИ І ПРОБЛЕМА ВАЛОРИЗАЦІЇ ВІДНОВЛЮВАНИХ ДЖЕРЕЛ ЕНЕРГІЇ В УКРАЇНІ - Костюк, В.О.; Шульженко, С.В.; Охріменко, І.А. (Інститут електродинаміки НАН України, Київ, 2014)
Variant computations of levelized cost of electricity (LCOE) generated by small photovoltaic power plants (PVPP) have been done within a frame of life cycle model representation. Estimates for payback period have been calculated basing on sensitivity analysis of LCOE and evaluation of discounted cash flow (DCF) curves. Resulting cumulated DCFs are collated to the consequent flow values provided the green feed-in-tariff (FiT) for ground based PVPP effective as of 01 April 2013 has been applied. The drawbacks of the effective green FiT system in Ukraine have been pointed out causing the unreasonable differentiation of electricity producers by technology of generation. References 3, figures 2.